William Henry Allison diaries - Allison, William Henry, 1870-1941.; Allison, Mary Ireland, -1870.
Diaries kept by Allison recording his daily activities as a historian at Bryn Mawr College, Colgate University, Pacific Theological Seminary, and other institutions; clergyman at Penacook Baptist Church, Concord, N.H.; and consultant to the Library of Congress in church history. Includes a diary (1868-1869) kept by his grandmother, Mary Ireland Allison.
Historian and clergyman.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bryn Mawr College -- Faculty; Colgate University -- Faculty; Library of Congress; Pacific Theological Seminary (Berkeley, Calif.) -- Faculty; Penacook Baptist Church (Concord, N.H.); Baptists -- Clergy; Baptists -- New Hampshire -- Concord; Church history; Clergy; Historians